The effect of Heweijiangni-decoction on esophageal morphology in a rat model of OVA-induced visceral hypersensitivity followed by acid exposure - Jia, Bo-yi; Xie, Chun-e; Wang, Zhi-bin; Pei, Wen-jing; Li, Xiao-hong; Shi, Lei; Liu, Jia-li; Han, Ya-fei; Tan, Xiang; Ding, Pang-hua; Sun, Zhong-mei; Yuan, Wen-jing; et al. (Cellular and Molecular Biology, 2019)
Heweijiangni decoction (HWJND) is an effective traditional Chinese medicine prescription in clinical treatment of nonerosive reflux disease (NERD). Esophageal hypersensitivity and acid contribute to the disease. However, the exact underlying mechanism of action remains unclear. In this study, we observed the effect of HWJND on esophageal morphology in a rat model of ovalbumin (OVA)-induced visceral hypersensitivity followed by acid exposure. Esophageal morphology was assessed by measuring the extent of dilated intercellular spaces (DIS), desmosome disruption, and mitochondrial fragmentation. HWJND in low, moderate, and high doses relieved DIS and desmosome disruption in esophageal epithelium compared with model group (P<0.05 for all doses). In addition, HWJND in high dose protected mitochondria from fragmentation (P<0.05). Other findings suggest that DIS and mitochondrial fragmentation are independent events, and that omeprazole protects mitochondria. Overall, HWJND significantly resists esophageal morphology changes in OVA-induced and acid exposure rat model.